Trends on primary TKA in Government Tertiary-Referral Hospitals 2019 - Reza Rahman Ramadhani; Dicky Mulyadi; Armia Indra Nur Alam; Cokorda Gde Oka Dharmayuda; Sholahuddin Rhatomy; Rizki Rahmadian; Muhammad Andry Usman; Chairiandi Siregar; Asep Santoso; Krisna Yuarno Phatama (Indonesian Hip and Knee Society (IHKS), 2020)
Background: Total knee arthroplasty (TKA) is the most common surgical option for end-stage knee OA with knee deformity and persistent pain. This procedure has already been increased in national insurance era. There are many conditions may affect the outcome of TKA include: the complexity or difficulty of the surgery or specific states of the affected limb. The difficult conditions in primary TKA are extra-articular deformity, severe coronal deformity, stiffness knee, neglected dislocation or patella subluxation, post-osteotomy (HTO or DFO), previous incision surgery. The paper aims to review the conditions which may adversely affect the usually excellent outcome of TKA.Methods: This is a descriptive study. The study describes the difficult or complex situation in primary TKA. The data for this study was obtained from the 9 Government Hospital in Indonesia. The patients receive surgery between January and December 2019.Results: Totally, there were 881 patients receive TKA in 9 government hospitals in Indonesia during 2019. From those, there were 221 difficult TKA cases 31,38%, and 600 were the simple case (68,11%). Severe coronal deformity are 183 cases. TKA with the stiff knee are 52 cases. Cases with wound problems or previous incision are 12 cases. Ekstra articular deformity are 15 cases. TKA post osteotomy are 9 cases. TKA with genu recurvatum are 6 case. TKA with patella dislocation or subluxation is 4 case.Conclusions: Almost one-third of primary TKA are difficult cases that need much more advanced technique and advance implant (more expensive) for more extended durability (avoid failure and costly-revision). National insurance coverage should recognize primary-difficult TKA.